Effect of bisacodyl on rats with slow transit constipation - Wang,Yong-bing (2018)
The effect of bisacodyl on the treatment of rats with slow transit constipation (STC) was studied. Forty-five female Wister rats were divided into control group, STC group, and STC bisacodyl group. The immunohistochemical method was used to determine interstitial cells of Cajal (ICC) and the expression of c-Kit protein. Body mass and the number of defecations were significantly decreased in the STC group compared with the control group on the 100th day after diphenoxylate administration, while dry weight of feces was significantly increased and the intestinal transit time was prolonged. There were significant differences in the number of defecations, dry weight of feces, and intestinal transit time among the three groups. The number of defecations was higher, dry weight of feces was lower, and intestinal transit time was shorter in the STC bisacodyl group compared to the STC group. In addition, ICC basement membrane dissolution occurred in the colon wall of the STC group. The connection between ICC and surrounding cells was destroyed, and the nucleus shrunken to different degrees. Moreover, c-Kit expression in the STC group was significantly lower than the control group. The connection between ICC and surrounding cells in the STC bisacodyl group was significantly stronger than the STC group, and the number of ICC and the expression of c-Kit were increased. Bisacodyl could reduce the severity of STC in rats by increasing the number of ICC and the expression of c-Kit.